(untitled) (American Journal of Innovation in Science and Engineering, 2024)
In mature fields like FA Field, addressing production decline involves strategic infill well drilling to boost output from active structures. The location and number of infill wells are determined through bubble map analysis during development planning. The research methodology includes calculating recovery factors, estimating remaining reserves, predicting production increases post-infill drilling, and assessing infill well impacts. FA currently operates 13 development wells yielding approximately 346 bbl/day. Calculations reveal 5.41 MMSTB in remaining reserves with a 22.55% recovery factor. Bubble and iso-saturation maps identified locations for INF-1 and INF-2 infill wells, affecting specific observation wells. INF-1’s placement near A-1, A-3, A-5, and A-7 resulted in a 10.69 BOPD decline offset by 54 BOPD additional production. INF-2, affecting 2 wells, saw a 6.37 BOPD drop and 44 BOPD increase. These scenarios illustrate how overlapping areas from infill wells decrease surrounding well production rates.In the base case scenario, without optimization, the recovery factor stands at 28.09%. With one infill well affecting 4 drainage radius, it rises to 29.6%; with two, to 30.92%.